Overlapping effects of miR-21 inhibition and drugs for idiopathic pulmonary fibrosis in the post-myocardial infarction setting. (14th October 2021) - Aimo, A; Iborra Egea, O; Passino, C; Emdin, M
Abstract: Background: Intracoronary infusion of a specific miR-21 inhibitor after reperfused MI has been reported to reduce cardiac fibrosis and hypertrophy and improve cardiac function in pigs. Possible drawbacks of anti-miR-21 therapy are the high costs of this therapy, and the need for intracoronary administration, preferably some days after reperfusion. Oral drugs with anti-fibrotic actions could have similar effects than anti-miR-21, while overcoming the limitations of anti-miR-21. We tested this hypothesis by examining the two oral drugs approved for idiopathic pulmonary fibrosis (nintedanib and pirfenidone). Methods: We identified the regulatory profile of miR-21, which included 588 target genes. Only 99 of these interactions were supported by information from reporter gene assays. The biological significance of these 99 targets was evaluated through over-representation analysis, and 13 genes were identified as potentially related to cardiovascular diseases. We retrieved all known targets and main downstream interactions of nintedanib and pirfenidone from Drugbank. Finally, we cross-validated these datasets by using neural network analyses to search for protein-protein interactions, focusing on those shared by miR-21 inhibition, nintedanib and pirfenidone. Results: Nintedanib and anti-miR21 had many targets in common, which could indicate an overlap in their corresponding mechanisms of action. The proto-oncogene SRC, which participates in gene transcription, immune response, apoptosis and migration, emerged as the leading signaling effector. By blocking SRC expression and many downstream effectors of SRC, as well as platelet-derived growth factor, nintedanib could decreased miR-21 expression. The molecular effects of nintedanib include inhibition of inflammation, fibrosis and angiogenesis, and then ultimately a relief from I/R injury, in a similar fashion than anti-miR-21. Contrary to nintedanib, no overlap between the effects of pirfenidone and anti-miR-21 was found. Conclusion: Because of the remarkably strong overlapping with the targets of miR-21, there is a stronger rationale to assess nintedanib than pirfenidone as a cardioprotective therapy. If confirmed by experimental evidence, nintedanib could enter the stage of clinical trials to assess its efficacy in human patients with STEMI. FUNDunding Acknowledgement: Type of funding sources: None.